MENINGKATKAN KEMANDIRIAN BELAJAR SISWA DENGAN MENGGUNAKAN LAYANAN KONSELING KELOMPOK - Rista Nalindra; Syaifuddin Latif; Diah Utaminingsih (ALIBKIN (Jurnal Bimbingan Konseling), 2013)
The purpose of this study to determine the increase of in independent learning using group counseling. The problem of this study is the low learning independence. The problem in this research is “Can study independence increase by using counselling group for the students at grade VIII SMPN 10 Kotabumi in academic year 2012/2013?”. The method that is used in this study with a quasi-experimental one-group pretest-posttest design. Subjects of the study of the six students who have a low learning independence. Technique in gained the data of this research is by using study scale independence of learning and Observation. The result shows that the studens’ independent learning can be enhanced by using group counseling, as evidenced from the analysis of the data by using the Wilcoxon test different, from the pretest and posttest results Obtained Zoutput Ztabel (-2201 0) then Ha is accepted, it means that independence of student learning can be enhanced by using group counseling services.Conclusion of this research is independence of student learning can increase by using counselling group of the students grade VIII SMPN 10 Kotabumi North Lampung regency Academic Year 2012/2013.The suggestion that can be given (1) for the students who has a low learning independence, one way to increase of independent learning by following a group counseling services in order to increase of the independence of learning, (2) for the teachers, group counseling services can be used to improve students’ learning independence. (3) for the Researchers should be Able to conduct research on learning independence issues with the condition of different subjects, but in conducting subsequent research use the same methods.Kata kunci : Bimbingan Konseling, Kemandirian Belajar, Konseling Kelompok.